Nilai Moral Moral, Lakon Kunthi NILAI MORAL LAKON KUNTHI PILIH DALAM SERAT PUSTAKARAJA SEBAGAI SARANA PENDIDIKAN KARAKTER - Hastini, Dite; Saputra, Danang (Widya Wacana : Jurnal Ilmiah, 2024)
This article contains a description of the moral values ​​found in Serat Pustakaraja by R.Ng.Ranggawarsita. The theory used is the theory of intrinsic elements in the narrative text of Panuti Sudjiman. The description of moral education is obtained based on an analysis of the intrinsic elements in the form of plot and plot of the Kunthi Choose play which is one of the stories in Serat Pustakaraja. Based on the plot analysis, moral values ​​are described in the form of proverbs or called unen-unen in Javanese. In the next story, these moral values ​​become the implementation of character education.